Determination of the Financial Literacy Characteristics of Prisoners: The Case of Turkey, a Developing Country - Umut Burak Geyikçi; Ahmet Tuğçin Uzuner; Seniye Geyikçi (Ceza Hukuku ve Kriminoloji Dergisi)
Increasing crime rates and prison occupancy are major problems for every country. Previous studies were conducted in countries with high national incomes. Therefore, there is a gap in the literature as to whether different results can be achieved in countries with different income levels. For this reason we aimed to determine whether the level of financial literacy differs between types of crimes, and, if there is a difference, which types of crimes are associated with low financial literacy. The quantitative data set consists of a survey conducted in February 2020, with 670 out of the 712 convicts incarcerated in the Manisa E-type closed penal institution in western Turkey who agreed to respond. Within the scope of the study, the basic and sophisticated financial literacy of convicts were measured and then basic and sophisticated literacy indices were created. There are 3 hypotheses in this context. H1: The convicts have lower financial literacy than the general public hypothesis is not rejected. H2: The level of basic financial literacy of convicts varies according to the types of crimes hypothesis is not rejected. H3: The convicts have lower levels of financial sophistication then other disadvantages groups hypothesis is rejected. Our financial literacy indices indicated that the prisoners’ basic financial literacy levels were closely related to various demographic factors whereas the level of financial sophistication was weakly related to them. Individuals imprisoned for grievous bodily harm and murder had the highest financial literacy levels, and were similar to levels in the general Public. Regarding sophisticated literacy, all respondents had high literacy levels for asset pricing, risk diversification, fees and deductions, and concepts.